Research on the Impact of Digital Inclusive Finance on the Income Gap between Urban and Rural Areas under the Background of National Unified Market - Zhang, Ruiqi (International Journal of Global Economics and Management, 2024)
In 2022, the "Opinions of the Central Committee of the Communist Party of China and the State Council on Accelerating the Construction of a National Unified Market" proposed the concept of a "unified market", which can effectively allocate resources to maximize social welfare. A national unified market with fair competition, a competitive venue and mechanism with non-monopoly and fair trading characteristics and functions. Since the reform and opening up, China’s economy has achieved sustained high-speed growth, and the goal of high-quality development in the new era has shifted to solving the problem of imbalanced and insufficient development, narrowing the gap between urban and rural regional development, achieving comprehensive human development, and achieving common prosperity for all people. In depth exploration of how to further promote rural revitalization and common prosperity has important practical significance and value. This article conducts theoretical analysis to propose research hypotheses, collects digital inclusive finance index and urban-rural income related data from 2013 to 2022, constructs the Theil index to measure urban-rural income gap, constructs a panel data model, studies the impact of digital inclusive finance on urban-rural income gap, verifies hypotheses, and concludes that digital inclusive finance should focus on development in the context of a unified national market.